2021
DOI: 10.1001/jamanetworkopen.2021.28971
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Use After Transitions of Care Among Young Adults With Sickle Cell Disease and Tennessee Medicaid Insurance

Abstract: and Smeltzer reported receiving grants from the National Heart, Lung, and Blood Institute and the Centers for Disease Control and Prevention during the conduct of the study. No other disclosures were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Our needs assessment focused on care redesign to improve hydroxyurea uptake and considered intervention targets, modalities, and strategy mechanisms. Barriers and enablers to hydroxyurea utilization in the SCD population were conducted through literature synthesis (19)(20)(21)(22), populationlevel claims analysis (13,23), patient and provider surveys (24,25), semi-structured interviews, and focus groups (16, 26). To synthesize and organize the needs assessment findings at the patient level, the Health Belief Model (HBM) (27) was used, and the Social Cognitive Theory (SCT) was used as the behavioral change model (28).…”
Section: Activity 1: Needs Assessment Of Hydroxyurea Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our needs assessment focused on care redesign to improve hydroxyurea uptake and considered intervention targets, modalities, and strategy mechanisms. Barriers and enablers to hydroxyurea utilization in the SCD population were conducted through literature synthesis (19)(20)(21)(22), populationlevel claims analysis (13,23), patient and provider surveys (24,25), semi-structured interviews, and focus groups (16, 26). To synthesize and organize the needs assessment findings at the patient level, the Health Belief Model (HBM) (27) was used, and the Social Cognitive Theory (SCT) was used as the behavioral change model (28).…”
Section: Activity 1: Needs Assessment Of Hydroxyurea Utilizationmentioning
confidence: 99%
“…As the first FDA-approved evidence-based drug for SCD, daily oral hydroxyurea is a medication recommended by guidelines (6) and with robust evidence for reducing acute and chronic disease complications, lowering acute-care utilization, and improving survival among individuals with SCD (7)(8)(9)(10)(11). In the U.S., <50% of patients with SCD appropriately utilize hydroxyurea (12)(13)(14)(15), severely limiting its population impact. SCDIC consortium members thus chose to focus on strategies to increase hydroxyurea uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about hydroxyurea 12 (25) Knowledge about hydroxyurea regimen 6 (13) Forgetfulness 13 (27) Get my child to take their hydroxyurea 10 (21)…”
Section: Psychological Capability 18 (38)mentioning
confidence: 99%
“…22 Prior studies reported poor medication adherence to HU, penicillin, and asthma medications in SCD, 19,23,24 particularly among adolescents and young adults (AYA). 25 Previously reported barriers to adherence include forgetfulness, fear of side effects, inability to obtain refills, and misperceptions of SCD severity. 16,[26][27][28][29][30][31][32][33][34] Many of the previous studies focused on HU adherence included smaller sample sizes and did not examine adherence challenges using an established conceptual model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation